Pengaruh Pemberian Ubi Jalar Ungu Terhadap Penurunan Tekanan Darah Pada Pasien Diabetes Mellitus Tipe 2 Di Tanjung Kemuning Iii Kecamatan Tanjung Kemuning Kabupaten Kaur - Rianti, Rianti; Eriestyana , Putri; Kartiwi , Lela; Sari , Novi Rufita; Oktapiasari , Lensi; Yanti , Sinta Fitri; Habibi , Julius; Fauzi , Yusran (Jurnal Kewirausahaan & Inovasi, 2026)
Diabetes mellitus (DM) is a growing public health problem both globally and nationally. This disease is characterized by high blood glucose levels due to impaired insulin secretion, insulin action, or both. The current trend is that the number of people with diabetes mellitus is increasing worldwide (Firani, 2022). The International Diabetes Federation reported in 2021 that 537 million adults (20-79 years old) were living with diabetes worldwide. This number is expected to increase to 643 million (1 in 9 adults) by 2030 and 784 million (1 in 8 adults) by 2045. Diabetes mellitus caused 6.7 million deaths in 2021. An estimated 44% of adults living with diabetes (240 million people) are undiagnosed. 541 million adults worldwide, or 1 in 10, have impaired glucose tolerance, putting them at high risk of developing type 2 diabetes (International Diabetes Federation, 2021). One important factor contributing to the rise in diabetes is diet. The shift in people's consumption patterns from traditional local foods to instant and ultra-processed foods is an increasingly visible phenomenon. One non-pharmacological approach that has the potential to help lower blood pressure is the provision of functional foods, including purple sweet potatoes. Purple sweet potatoes are rich in anthocyanins, fiber, and antioxidants, which can improve endothelial function, reduce oxidative stress, and improve glucose and lipid metabolism. Anthocyanins are known to have vasodilatory and anti-inflammatory effects that can contribute to lowering blood pressure. Thus, purple sweet potato supplementation has the potential to be a cheap, easy, safe, and locally sourced intervention to help control blood pressure in patients with type 2 diabetes mellitus. Based on data from the Tanjung Kemuning Community Health Center and data from the Village Midwife from January to April 2024, there were 8 cases of diabetes mellitus in Tanjung Kemuning III Village, Tanjung Kemuning District. Therefore, based on the available data, this diabetes mellitus counseling and diabetes mellitus exercise program was conducted in Tanjung Kemuning III Village, targeting the elderly and pre-elderly who already have diabetes mellitus or are at risk of developing it.